3D Imaging for Safety and Security - Koschan, Andreas; Pollefeys, Marc; Abidi, Mongi (Computational Imaging and Vision, 2007)
The past decades have seen significant improvements in 3D imaging where the related techniques and technologies have advanced to a mature state. These exciting developments have sparked increasing interest in industry and academia in the challenges and opportunities afforded by 3D sensing. As a consequence, the emerging area of safety and security related imaging incorporates these important new technologies beyond the limitations of 2D image processing. This book is so far the first that covers the current state of the art in 3D imaging for safety and security. It reports about selected contributions given at the "Workshop on Advanced 3D Imaging for Safety and Security" held in conjunction with the International Conference on Computer Vision and Pattern Recognition CVPR 2005, June 2005, San Diego, CA. The workshop brought together pioneering academic and industrial researchers in the field of computer vision and image analysis. Special attention was given to advanced 3D imaging technologies in the context of safety and security applications. Comparative evaluation studies showing advantages of 3D imaging over traditional 2D imaging for a given computer vision or pattern recognition task were emphasized. Moreover, additional experts in the field of 3D imaging for safety and security were invited by the editors for a contribution to this book. The book is structured into two parts, each containing five or six chapters on (1) Biometrics and (2) Safety and Security Applications.